COMPREHENSIVE INSIGHTS INTO MODERN COMPOSITE BINDERS: TYPES, PRODUCTION BASES, PROPERTIES, AND APPLICATIONS OF PORTLAND CEMENT-BASED COMPOSITES - Ergashev Mahmudjon Mamadjanovich (American Journals Publishing, 2023)
This study provides a comprehensive examination of modern composite binders, with a specific focus on Portland cement-based compositions. The research explores the diverse types of composite binders, elucidating their production bases, inherent properties, and versatile applications. Through an in-depth analysis, the study identifies key characteristics that define these composite binders, ranging from their chemical compositions to mechanical properties. The production processes, including raw material selection and manufacturing techniques, are scrutinized to unveil the intricacies of creating these advanced binders. Furthermore, the research sheds light on the specific areas of application where these modern composite binders exhibit superior performance. This includes considerations for construction, infrastructure development, and various industries where the unique properties of Portland cement-based composites find innovative use. The insights garnered from this study contribute to an enhanced understanding of the modern composite binder landscape, offering valuable knowledge for researchers, industry professionals, and practitioners involved in the development and application of advanced construction materials.
Keywords: Composite binders, portland cement, construction materials, production processes, material properties, infrastructure development, cement-based composites, advanced binders, manufacturing techniques, mechanical properties, concrete technology, building industry.